PROPUESTA DE UN PLAN DE MARKETING TURÍSTICO DE LOS ATRACTIVOS NATURALES DEL CANTÓN QUILANGA, DE LA PROVINCIA DE LOJA, 2015 - Paladinez Riofrio, Yoselin Gissella (2016)
In the province of Loja there are valleys of wealth and natural beauty can be seen in a cold Andean plateau and the other the warmth of a coastal region, this particular results in the diversity of fauna and flora life, providing them with beautiful places, scenic beauty and landscape. Within the 16 cantons that make up the province of Loja is the canton Quilanga, a place that has really striking natural attractions to capture the local and national economy, why it is important to encourage them and disseminate them. For the development of this study was necessary to raise a general objective and three specific goals that helped them correct progress of work and consequently its results, for this reason the overall objective was aimed at "Developing a Marketing Plan Tourist attraction Natural Quilanga Canton province of Loja ". In the present research work all the processes of scientific research, the same as were met fully developed. To fulfill the first objective "Making a diagnosis of the current situation of the natural attractions of the canton Quilanga province of Loja. "Chips inventory MINTUR, in order to know the current situation of the attractions was used, as it was also necessary to apply a summary tab and a tab of hierarchy, where it was known the potential value thereof. Besides the inductive and deductive method was used to know the most relevant facts and therefore the conclusions of the project was obtained; in techniques, SWOT, strategy matrix and direct observation was used, determining the current status of the canton and its attractions, plus the corresponding surveys and interviews conducted. In compliance with the second objective "To propose a Plan of Tourist Marketing of Natural Attractions Quilanga Canton province of Loja." Deductive method was made using information collected in the diagnosis of attractions; using the results obtained through the SWOT matrix strategies in order to have the best alternatives of promotion and marketing proposal took place. For the third goal, "he Socialize the Tourism Marketing Plan for Natural Attractions Canton Quilanga province of Loja to the cantonal authorities and the community in general.", It was necessary to make a formal visit to the village in order to present the results deductive method and suggestions were obtained. Finally, conclusions let me point out that it is important to make the updated diagnosis of the tourist attractions the county has Quilanga. The development of the Marketing Plan is a tool to promote and disseminate the natural attractions of the canton Quilanga, both locally and nationally, for it must be consistent with the current market trends. Based on the socialization performed, it is considered to be implementing training everyone involved in the tourism sector, so that they can provide excellent service. This thesis project is the first proposal of a tourism marketing plan for the natural attractions of the canton Quilanga indispensable tool that will contribute to tourism development in the county in order to position it as a tourism destination in the region and the country in July. While some of the recommendations made at the end of this work are that the Ministry of 5 Tourism Zone 7, perform periodic updating of both places inside the canton as of tourist services offered, so you can find truthful information, reposed in the Department of MINTUR. It is recommended to Quilanga Decentralized Autonomous Government, to use tourism brand owned by the canton also develop advertising for television and the Internet, brochures, posters; for the promotion caps, thread woven handicrafts, video, postcards and mugs. GAD Canton Quilanga and the Ministry of Tourism Zone 7, designate an annual budget, to carry out training plans for native guides may have his license as such, the artisans, to preserve the art of weaving in thread, and tour suppliers to provide a good service to tourists, along with accurate and timely information. The agreement between the GAD Quilanga Canton and the National University of Loja is maintained, so that they continue to develop projects for the benefit of the canton.